Analisis Pelaksanaan Komunikasi Efektif SBAR Perawat dan Dokter - Nirta Aprila Paembonan; Erfina Erfina; Ariyanti Saleh (Journal of Telenursing (JOTING), 2023)
The aim of this research is to map research results related to the implementation of effective SBAR communication between nurses and doctors. The research method used, namely Scoping Review, was used to map the literature using PRISMA guidelines. The synthesis method uses PCC modification. Articles obtained from the Google Scholar search engine as well as the electronic databases PubMed and ScienceDirect. Search results, from 87 relevant articles with titles and abstracts, 6 articles were found that met the inclusion and exclusion criteria. The research results found that the analysis of the implementation of effective SBAR communication between nurses and doctors contained seven themes, namely patient safety and satisfaction, lack of self-confidence, environment, lack of interpersonal communication, lack of training, and work safety climate. In conclusion, effective communication and collaboration between doctors and nurses is very necessary in managing and limiting disturbances that can endanger patient safety and the continuity of safe care for at-risk patients. Keywords: Implementation Analysis, Effective Communication, SBAR